Balloon valvuloplasty as destination therapy in elderly with severe aortic stenosis: a cardiac catheterization study - Kamperidis, Vasileios (J Geriatr Cardiol, 2015)
BACKGROUND: In the current era of transcatheter aortic valve replacement, there is renewed interest in balloon aortic valvuloplasty (BAV) and invasive hemodynamic evaluation of aortic stenosis (AS). The current report aimed to study the invasive hemodynamics of severe AS patients treated with BAV as destination therapy and to identify factors associated with better hemodynamic outcome and prognosis. METHODS: From 2009 to 2012, 63 high risk elderly patients were treated with BAV as destination therapy for symptomatic severe AS and were all prospectively included in the study. Their hemodynamics were invasively evaluated during catheterization, pre- and post-BAV at the same session. All Post-BAV patients were regularly followed-up. RESULTS: The patients (82 ± 6 years, 52% male) had post-BAV aortic valve area index (AVAi) significantly increased and mean pressure gradient (MPG) significantly reduced. During the follow-up of 0.9 (maximum 3.3) years, those with post-BAV AVAi < 0.6 cm(2)/m(2) compared with the AVAi ≥ 0.6 cm(2)/m(2) group had significantly higher mortality (60% vs. 28%, log-rank P = 0.02), even after adjusting for age, gender, atrial fibrillation, chronic kidney disease, diabetes mellitus, coronary artery disease and EuroSCORE [HR: 5.58, 95% confidence interval (CI): 1.62−19.20, P = 0.006]. The only independent predictor of moderate AS post-BAV was the pre-BAV AVAi increase by 0.1cm(2)/m(2) (OR: 3.81, 95% CI: 1.33−10.89, P = 0.01). Pre-BAV AVAi ≥ 0.39 cm(2)/m(2) could predict with sensitivity 84% and specificity 70% the post-BAV hemodynamic outcome. CONCLUSIONS: BAV as destination therapy for severe AS offered immediate and significant hemodynamic improvement. The survival was significantly better when a moderate degree of AS was present.